Factors affecting seropositivity to human T cell lymphotropic virus type III (HTLV-III) or lymphadenopathy associated virus (LAV) and progression of disease in sexual partners of patients with AIDS. - Weber, J N (1986)
Fifty four sexual partners of homosexual men with the acquired immune deficiency syndrome (AIDS) were studied, of whom 32 were seropositive and 22 seronegative for human T cell lymphotropic virus type III or lymphadenopathy virus (HTLV-III/LAV) antibody, which showed that repeated exposure by anal intercourse does not necessarily lead to seroconversion. Seropositivity to HTLV-III/LAV was not associated with the absolute number of sexual partners, receptive anal intercourse, or the use of recreational drugs, but was associated with a history of other sexually transmitted diseases (STDs), particularly in the year preceding the patient's initial examination. Acquisition of an STD after the date of last sexual contact with a person with AIDS was strongly associated (p less than 0.001) with the development of persistent generalised lymphadenopathy (PGL). Concurrent or recent STDs would seem to be an important cofactor in developing antibody to HTLV-III/LAV and in the progression of infection from a person being asymptomatic to having PGL.